Environmental impact technology for life cycle assessment in municipal solid waste management - M.A. Budihardjo; I.B. Priyambada; A. Chegenizadeh; S. Al Qadar; A.S. Puspita (Global Journal of Environmental Science and Management)
Municipal solid waste management has evolved from direct disposal to recycling and resource recovery, driven by sustainability. Life cycle assessment has played a crucial role in analyzing the environmental implications of different waste management strategies and selecting the most ecologically feasible options. Establishing best practices in municipal solid waste management based on competent life cycle assessment work is essential for policymakers to make informed decisions. This study reviewed 34 life cycle assessment studies on solid waste management systems in Asian countries, examining their life cycle stages, assessment techniques, and key outcomes. The analysis highlights include functional units, various life cycle assessment models (such as SimaPro and GaBi), life cycle impact assessment methods, impact categories, and alternative waste management methods. It is necessary to prioritize recycling, resource generation (such as decomposition, incineration, and anaerobic digestion), and waste reduction over landfilling to attain a high level of environmental friendliness. However, it is essential to observe that technologies necessitating large upfront investments and skilled labor are better suited for high-income countries. Conversely, low-income countries should prioritize waste reduction through recycling, waste depots, and methods that correlate with their existing capabilities to reduce the amount of waste sent to landfills. By sharing existing methods, developing integrated municipal solid waste management systems can be accelerated in low-income nations, which can have a substantial positive economic impact. Therefore, decision-makers should consider social, economic, and environmental impacts when selecting an appropriate refuse management strategy for their nation. This analysis provides valuable insights into the scope of life cycle assessment studies and contributes to the selection of sustainable municipal solid waste management systems. These findings can be utilized by life cycle assessment practitioners, stakeholders, and Asian governments to inform policy development and decision-making processes.